The variation of the Firm’s value considering the relationship between the financial structure and earnings per share - Kadim Alkhalidi, Fatima Faisal; Mohammed Aljubori, Ayad Taher (Journal of Economics and Administrative Sciences, 2021)
The current research aims to determine the relationship of the impact of the components of the financing structure, especially financing through debts, as well as the earnings per share in the value of the shares of companies listed in the Iraq Stock Exchange. The research sample and identifying the strength of the combined effect of the ratio of financing through debt and earnings per share in maximizing The market value of the firm and the real value, as well as the variation between these relationships according to model of the real value of the companies and the market value of the research sample companies. The research community is represented by the Iraq Stock Exchange, while a conditional deliberate sample was selected that included (10) companies, and data and information were collected through the annual financial reports issued by the Iraq Stock Exchange for the time period (2014-2018), as well as The research relied on a set of descriptive statistics methods (arithmetic mean - standard deviation - percentages) as well as a group of inferential statistics methods (Pearson Correlation Laboratory - Simple Regression - Multiple Regression), through the two statistical packages of (SPSS V.26 - AMOS V. 25) to compare the calculated results and test the hypotheses. The research found the most prominent results represented in the absence of an effect of the debt ratio on the market and real value of companies, while it found a significant effect of the debt ratio and earnings per share on the market value of companies. The importance of the research is represented by the limited studies that dealt with the three variables together in an analytical manner in the Iraq Stock Exchange (financing structure - earnings per share - firm value) and the extent of the impact of each of the financing structure through the debt ratio, and earnings per share on both market value and real value For companies' shares, as well as determining the relationship between the independent research variables represented by the financing structure and earnings per share, with the approved variables (the real value of companies, and the market value)